Insights from engraftable immunodeficient mouse models of hyperinsulinaemia - Michelle L. Maugham (Nature Portfolio, 2017)
Abstract Hyperinsulinaemia, obesity and dyslipidaemia are independent and collective risk factors for many cancers. Here, the long-term effects of a 23% Western high-fat diet (HFD) in two immunodeficient mouse strains (NOD/SCID and Rag1 −/−) suitable for engraftment with human-derived tissue xenografts, and the effect of diet-induced hyperinsulinaemia on human prostate cancer cell line xenograft growth, were investigated. Rag1 −/−and NOD/SCID HFD-fed mice demonstrated diet-induced impairments in glucose tolerance at 16 and 23 weeks post weaning. Rag1 −/− mice developed significantly higher fasting insulin levels (2.16 ± 1.01 ng/ml, P = 0.01) and increased insulin resistance (6.70 ± 1.68 HOMA-IR, P = 0.01) compared to low-fat chow-fed mice (0.71 ± 0.12 ng/ml and 2.91 ± 0.42 HOMA-IR). This was not observed in the NOD/SCID strain. Hepatic steatosis was more extensive in Rag1 −/− HFD-fed mice compared to NOD/SCID mice. Intramyocellular lipid storage was increased in Rag1 −/− HFD-fed mice, but not in NOD/SCID mice. In Rag1 −/− HFD-fed mice, LNCaP xenograft tumours grew more rapidly compared to low-fat chow-fed mice. This is the first characterisation of the metabolic effects of long-term Western HFD in two mouse strains suitable for xenograft studies. We conclude that Rag1 −/− mice are an appropriate and novel xenograft model for studying the relationship between cancer and hyperinsulinaemia.